Drug Testing, Sex Verification, and the 1967 Pan-American Games. Issue 1 (22nd January 2016) - Teetzel, Sarah; Torres, Cesar R.
Abstract: Despite frequent claims that invasive methods of sex verification and early procedures for doping detection were used in 1966 and 1967 at different major international sport competitions, little is known about the origins and rationales for implementing such procedures. This paper focuses on the drug testing and sex verification protocols implemented at the 1967 Pan-American Games held in Winnipeg. Specifically, it explores the conditions that led to these protocols, as well as the details of and the arguments invoked for their implementation. To do so, archival material, media coverage featured in English, French, Portuguese, and Spanish newspapers and magazines across the Americas, and oral histories are analyzed and discussed. The paper demonstrates that neither the sex verification nor the drug testing protocol was mandatory for all athletes and only two very specific groups of athletes were targeted. It also demonstrates that in the case of the former, exceptions were made within the specific group targeted. The paper concludes that the rudimentary protocols applied at the 1967 Pan-American Games likely informed the IOC Medical Commission's doping and sex-testing policies implemented at the 1968 Mexico City Olympics and Grenoble Winter Olympics.